Juridical Analysis Changes Number Minimum and Maximum Sanctions Corruption Against Justice and Legal Certainty - Elia, Christopher; Kholiq, Abdul (Law Development Journal, 2025)
This study aims to analyze the juridical comparison of changes in the minimum and maximum sanctions for corruption crimes in the new Indonesian Criminal Code (Law Number 1 of 2023) compared to the Anti-Corruption Law (Law Number 31 of 1999 juncto Law Number 20 of 2001). The research seeks to examine how these changes affect the principles of justice and legal certainty amid Indonesia’s ongoing struggle with corruption. The research method was used a normative juridical approach with legislative, conceptual, and case approaches. Data were obtained from primary, secondary, and tertiary legal materials through literature study, and analyzed using qualitative, content, and descriptive analysis techniques. The novelty of this research lies in its comprehensive analysis of both the minimum and maximum criminal sanctions, supported by factual data such as corruption case trends, the Anti-Corruption Behavior Index, and the interpretation of Decision Number 1/Pid.Sus-TPK/2024/PN Mam. This study also introduces adaptive solutions through penal and non-penal measures, such as asset forfeiture, revocation of political rights, and restrictions on public office, to strengthen deterrence and restore justice. Based on the research concluded that the reduction of sanctions for corruption crimes in the new Criminal Code is inconsistent with Indonesia’s corruption reality and requires refinement to ensure the balance between justice, legal certainty, and the effectiveness of corruption eradication.